Исследование работы двухконтурной системы управления компенсатором неактивных составляющих полной мощности - Левон, Елена Александровна; Козлов, Сергей Сергеевич; Римарь, Сергей Иванович; Кузьменко, Наталья Алексеевна (Національний технічний університет "Харківський політехнічний інститут", 2020)
В статье представлена модель полупроводникового компенсатора с дополнительным контуром нечеткого регулирования по уровню высших гармоник тока питающей сети. Модель создана и апробирована в пакете MATLAB 7.0.1. Исследованы зависимости уровня коммутационных перенапряжений, а также уровня амплитуды отдельно взятой гармоники тока питающей сети от относительного напряжения на конденсаторе накопителя. Показана возможность эффективного управления уровнем амплитуды отдельно взятой гармоники тока питающей сети. Получены с помощью моделирования графические зависимости, произведен их анализ, что подтвердило теоретические выводы, которые необходимо учитывать при настройке параметров нечеткого контроллера. Доказана возможность адаптации предложенной цифровой системы управления в переменных условиях энергосистемы, благодаря применению дополнительного контура регулирования уровня отдельно взятой гармоники.

The article presents a model of a semiconductor compensator with an additional fuzzy control loop for the level of higher harmonics of the supply network current. The model was created and tested in the MATLAB 7.0.1 package. The dependences of the level of switching overvoltages, as well as the level of the amplitude of a single harmonic of the current of the supply network, on the relative voltage across the storage capacitor are investigated. The possibility of effective control of the amplitude level of a separate harmonic of the supply network current is shown. Graphical dependencies were obtained by means of modeling, their analysis was carried out, which confirmed the theoretical conclusions that must be taken into account when setting the parameters of a fuzzy controller. The use of an additional control loop for the level of a single harmonic makes it possible to adapt the proposed digital control system to varying conditions of the power system. The ability to adapt the pro-proponated digital control system in the energy system’s minus has been brought to the table, and the additional contour to regulate the level of the taken harmonic system has been added.
Research of the operation of a two-circuit control system of the compensator of inactive components of the full power
Keywords: полупроводниковый компенсатор; система управления; моделирование; гармоники тока; semiconductor compensator; control system; simulation; current harmonics